Trend Penelitian Keterampilan Berbahasa Dan Blended Learning Masa Lalu, Masa Kini Dan Masa Depan - Atrianing Yessi Wijayanti; Nimas Puspitasari (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2026)
This research examines the latest trends in Indonesian language education research in the past, present and future based on the topic, subject and research method used. The purpose of this study is to describe the trend of past, present and future research in Indonesian language education research. Past research topics on language skills were dominated by school children and as research subjects, while topics on blended learning were dominated by students as research subjects. The research method in the past year (2015-2018) was dominated by research with a case study approach, while the present year (2019-2021) was dominated by an experimental approach. The trend of research in the latest Indonesian language education in the future will be influenced by the rapid development of science and technology which will encourage innovation in learning. The Covid-19 pandemic will also have an impact on the learning methods and approaches used. The learning model in the future will be dominated by blended learning by utilizing technology for distance learning. Research subjects in future Indonesian language education research will also be dominated by students at the basic education level. This is in accordance with the idea that when students are at the elementary level, it is the most appropriate time to develop their understanding and thinking about language.Keywords: Trend, Indonesian Language Education